2017
DOI: 10.1002/jppr.1289
|View full text |Cite
|
Sign up to set email alerts
|

Using domperidone to increase breast milk supply: a clinical practice survey of Australian neonatal units

Abstract: Background Domperidone may be used off‐label to increase breastmilk supply. In the absence of manufacturer dosage recommendations, there is a need to compare the clinical practice guidelines used in Australian hospitals. Aim To compare existing clinical practice guidelines regarding the use of domperidone for increasing maternal breastmilk supply within Australian neonatal units (NNUs). Methods An electronic survey was distributed from April to July 2015 to relevant staff at each Level III NNU across Australia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…In addition, eligible studies where domperidone was prescribed for a minimum of 5 days following randomisation. The minimum duration of treatment was determined to be 5 days as this reflects the shortest duration of treatment identified in a recent clinical practice survey . Studies published only as abstracts were eligible for inclusion providing there was sufficient information presented in the abstract to demonstrate that the study met the inclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, eligible studies where domperidone was prescribed for a minimum of 5 days following randomisation. The minimum duration of treatment was determined to be 5 days as this reflects the shortest duration of treatment identified in a recent clinical practice survey . Studies published only as abstracts were eligible for inclusion providing there was sufficient information presented in the abstract to demonstrate that the study met the inclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…6 Previous studies have demonstrated that use of domperidone is widespread [7][8][9] with a recent clinical practice survey from Australia and New Zealand identifying that domperidone is considered the first-line in the treatment of low milk supply in the Neonatal Unit setting. 10 Despite high frequency of use, controversy surrounds the use of domperidone, with key issues related to the regulatory status of domperidone. 11 Domperidone has been the subject of regulatory warnings due to concerns regarding its QTc interval prolongation effects, but the relevance of these findings to younger, healthier lactating women has been questioned.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment durations range from 7 days to 6 weeks, although longer durations are seen in practice. There is an absence of evidence for one approach over another . Treatment should be tailored to the individual, based on identified risk factors or causes of low milk supply.…”
Section: Breast Milk Supplymentioning
confidence: 99%
“…While non‐pharmacological strategies remain first‐line approaches to increasing breast milk supply, pharmacological treatment with medications used to augment lactation, known as galactagogues, are commonly recommended . The most frequently utilised galactagogue in clinical practice is domperidone, followed by use of metoclopramide or herbal medications such as fenugreek or milk thistle. While data on use of such galactagogues in clinical practice remains scarce, data from an Australian tertiary level maternity hospital demonstrated a significant increase in the number of women dispensed domperidone, from <0.5% in 2000 to >5% of total pregnancies in 2010, with approximately 50% of use among mothers of infants admitted to neonatal intensive care or special care units .…”
Section: Introductionmentioning
confidence: 99%